Pulmonary vein isolation by irreversible electroporation: an efficacy and safety study in 20 patients with atrial fibrillation. (24th May 2021) - Loh, P; Groen, MHA; Taha, K; Wittkampf, FHM; Doevendans, PA; Van Es, R
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Irreversible electroporation (IRE) is a promising new non-thermal ablation technology for pulmonary vein isolation (PVI) in patients with atrial fibrillation (AF). First in human studies demonstrated the feasibility and safety of IRE PVI. Objective: Further investigate the safety of IRE PVI. Methods: Twenty patients with symptomatic AF underwent IRE PVI under conscious sedation. Oral anticoagulation was uninterrupted and heparin was administered to maintain activated clotting time at 300-350 seconds. Non-arcing, non-barotraumatic 6 ms, 200 J IRE applications were delivered via a custom non-steerable 8 F, 14-polar circular IRE ablation catheter with a variable hoop diameter (16-27 mm). Voltage mapping  of the left atrium and the PVs was performed before and after ablation with a conventional circular mapping catheter. For both catheters a single transseptal access (8 F introducer, Agilis NxTTM) was used. Adenosine testing was performed after a 30-minute waiting period. On day 1 after ablation, patients underwent esophagoscopy and brain MRI (DWI/FLAIR). If abnormalities were detected, examinations were repeated in due time. Results: In 20 patients, all 80 PVs could be successfully isolated with a mean of 11, 8 ± 1, 4 IRE applications per patient. Average time from first to last IRE application was 22 ± 5 minutes, total procedure duration was 107 ± 13 minutes and total fluoroscopy time was 23 ± 5 minutes. One PV reconnection occurred during adenosine testing, re-isolation was achieved with 2 additional IRE pulses. No periprocedural complications were observed. Brain MRI on day 1 after ablation showed punctate asymptomatic lesions in 3/20 patients (15%). At follow-up MRI the lesion disappeared in 1 patient while in the other 2 patients 1 lesion persisted. Esophagoscopy on day 1 showed an asymptomatic esophageal lesion in 1/20 patients (5%), at repeat esophagoscopy on day 22 the lesion had resolved completely. Conclusion: Acute electrical PV isolation could be achieved safely and rapidly by IRE ablation under conscious sedation in 20 patients with symptomatic AF. Acute silent cerebral lesions were detected in 3/20 patients (15%) and may be due to ablation or to changes of therapeutic and diagnostic catheters over a single transseptal access.